Teacher Identity (Re) Construction within Professional Learning Communities: The Role of Emotions and Tensions - Gedik, Pinar Kocabas; Ortactepe, Deniz (IGI GLOBAL, 2017)
The research on teacher professional identity mostly focused on the process of teacher professional identity formation, the characteristics of teacher professional identity according to the teachers themselves as well as the researchers, and the representation of professional identity through teacher narratives in written and spoken discourse (Beijaard et al., 2004). However, there is much to explore in teachers' tensions and emotions regarding the issues between teacher cognition, and personal and professional sides of teacher identity (Day & Leitch, 2001). In this chapter, we have reviewed the literature on teacher professional identity in relation to communities of practice, imagined identity, and imagined communities. Various definitions of emotions and tensions as well as their roles in teacher professional identity construction have been presented and relevant studies on teacher identity construction, emotions and tensions have been discussed.
Keywords: EDUCATORS; CONTEXT; Education & Educational Research